Physical Activity in Hospitalised Stroke Patients - Tanya West; Julie Bernhardt (Stroke Research and Treatment)
The aim of this paper was to examine the amount and type of physical activity engaged in by people hospitalised after stroke. Method. We systematically reviewed the literature for observational studies describing the physical activity of stroke patients. Results. Behavioural mapping, video recording and therapist report are used to monitor activity levels in hospitalised stroke patients in the 24 included studies. Most of the patient day is spent inactive (median 48.1%, IQR 39.6%–69.3%), alone (median 53.7%, IQR 44.2%–60.6%) and in their bedroom (median 56.5%, IQR 45.2%–72.5%). Approximately one hour per day is spent in physiotherapy (median 63.2 minutes, IQR 36.0–79.5) and occupational therapy (median 57.0 minutes, IQR 25.1–58.5). Even in formal therapy sessions limited time is spent in moderate to high level physical activity. Low levels of physical activity appear more common in patients within 14 days post-stroke and those admitted to conventional care. Conclusions. Physical activity levels are low in hospitalised stroke patients. Improving the description and classification of post stroke physical activity would enhance our ability to pool data across observational studies. The importance of increasing activity levels and the effectiveness of interventions to increase physical activity after stroke need to be tested further.